Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acs.cgd.7b01550
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Vapor-Mediated Phase Transition of the High Temperature Form of Pyrazinamide

Abstract: Tailor-made additives can prove an effective method to prolong the lifetime of metastable forms of pharmaceutical compounds by surface stabilization. Pyrazinamide (PZA) is a pharmaceutical compound with four polymorphic forms. The high temperature γ form, which can be produced by spray drying or sublimation growth, is metastable at room temperature and transforms within days when produced by spray drying, and within several months up to years for single crystals produced by sublimation. However, when PZA is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…11(b), which shows that these types of transitions can be tailored by impurities. Impurities are typically used to bind to surfaces and block certain processes (Weissbuch et al, 1991;Smets et al, 2018); here, they impact on the bulk properties and hence a much larger concentration is required. For the low-temperature $ transition, which is a 'pure shift' transition, no significant effect could be observed, but the variability from crystal to crystal is much larger for this transition and a 2-3 K change would not be observable.…”
Section: Figure 10mentioning
confidence: 99%
“…11(b), which shows that these types of transitions can be tailored by impurities. Impurities are typically used to bind to surfaces and block certain processes (Weissbuch et al, 1991;Smets et al, 2018); here, they impact on the bulk properties and hence a much larger concentration is required. For the low-temperature $ transition, which is a 'pure shift' transition, no significant effect could be observed, but the variability from crystal to crystal is much larger for this transition and a 2-3 K change would not be observable.…”
Section: Figure 10mentioning
confidence: 99%
“…For α and d, no transformations under pressure have been observed up to 13 GPa (Tan et al, 2012). Smets et al investigated the transformation mechanism of PZA and concluded that the transition from the g form to the low temperature d and a forms include a vapor-mediated recrystallization process, while the transition from the low temperature forms to the g form during heating included nucleation and growth within the crystal (Smets et al, 2018).…”
Section: P1 "mentioning
confidence: 99%
“…Because g is a metastable form of PZA under ambient conditions, which is easily obtained through processing, it may be an interesting target to increase the bioavailability of PZA, although the polymorph does not persist for a long time under ambient conditions (Baaklini, 2015;Baaklini et al, 2015;Smets et al, 2018). Baaklini et al have investigated polymorph control by spray drying with different additives and they managed to prevent spontaneous transformation of g. They also found that the g form persists at room temperature for several years by co-spray drying with 1,3-dimethylurea (Baaklini, 2015;Baaklini et al, 2015).…”
Section: P1 "mentioning
confidence: 99%
“…Solid–solid polymorphic transitions ubiquitously exist in organic and inorganic crystals related to photoelectric materials, , pharmaceuticals, and energetic materials . Since the properties of materials could be significantly changed accompanied by the polymorphic transition, understanding how the phase transforms and how to stabilize the phase form are fundamental questions in the research field correlated with polymorphic crystals. , Various reports have demonstrated that the polymorphic transition can be tuned through substitution of some ions or doping with other particular ions. However, this strategy is not suitable for organic molecular crystals. Except for the ion-doping strategy, researchers found that the polymorphic transition can be efficiently inhibited by surface functionalization. ,, For example, Li successfully demonstrated that surface coordination was an effective route to stabilize the monoclinic phase of VO 2 from converting to rutile phase by coordinating l -ascorbic acid on VO 2 nanobeam .…”
Section: Introductionmentioning
confidence: 99%
“…4 Since the properties of materials could be significantly changed accompanied by the polymorphic transition, understanding how the phase transforms and how to stabilize the phase form are fundamental questions in the research field correlated with polymorphic crystals. 3,6 Various reports have demonstrated that the polymorphic transition can be tuned through substitution of some ions or doping with other particular ions. 7−9 However, this strategy is not suitable for organic molecular crystals.…”
Section: Introductionmentioning
confidence: 99%